Maternal and child health performance of a national community health workers' program using large administrative databases: a quantitative case study of Afghanistan - Maisam Najafizada; Beth Potter; Ivy L Bourgeault; Ronald Labonte (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Community health workers (CHW) are an established workforce in many low- and middle-income countries (LMICs). Some countries with national CHW programs are Brazil, India, Nepal, Ethiopia, Pakistan, Bangladesh, Iran, and Afghanistan. These large-scale CHW programs are often evaluated using data from individual CHWs rather than the program. There is a dearth of quantitative research on national CHW programs using health-related administrative datasets. The purpose of this paper is to describe geographical distribution of CHWs, the volume of their activities, and the relationship of their activities with recorded maternal and neonatal deaths in rural Afghanistan between 2009 and 2012. # Methods This paper is a quantitative analysis of national CHWs program using a large administrative database from the Afghan Ministry of Public Health linked to population census data from Afghanistan. # Results We found that CHWs and the aggregate volume of their activities have increased between 2009 and 2012 in rural Afghanistan. CHWs are not equitably distributed by population size in the 34 provinces of the country. Recorded maternal and neonatal deaths have shown an increase from 2009 to 2011 and a decrease from 2011 to 2012. # Conclusion Large administrative datasets are important data sources for research with a potential to offer valuable lessons for policymakers and health managers. Despite methodological and quality challenges, this study can be used as a baseline for future replications, a point of comparison for future research on national CHW programs for other countries.